2005
DOI: 10.4049/jimmunol.175.4.2459
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Three HIV-1 HLA-B*5703-Peptide Complexes and Identification of Related HLAs Potentially Associated with Long-Term Nonprogression

Abstract: Long-term nonprogression during acute HIV infection has been strongly associated with HLA-B*5701 or HLA-B*5703. In this study, we present the high resolution crystal structures of HLA-B*5703 complexes with three HIV-1 epitopes: ISPRTLNAW (ISP), KAFSPEVIPMF (KAF-11), and KAFSPEVI (KAF-8). These reveal peptide anchoring at position 2 and their C termini. The different peptide lengths and primary sequences are accommodated by variation in the specific contacts made to the HLA-B*5703, flexibility in water structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 56 publications
5
72
0
Order By: Relevance
“…These particular alleles have been strongly associated with slow progression to disease and thus theoretically would exert a strong selective pressure on the virus (53 (52,56,61,81). The positively selected mutation in clade A1, A163G at the P2 anchor position of the KAF11 and KAF8 epitopes, is highly correlated with patients expressing HLA-B*5703 (P ϭ 3.21 ϫ 10 Ϫ8 ).…”
Section: Fig 1 Comparison Of Individual Residue Entropies Between Tmentioning
confidence: 78%
“…These particular alleles have been strongly associated with slow progression to disease and thus theoretically would exert a strong selective pressure on the virus (53 (52,56,61,81). The positively selected mutation in clade A1, A163G at the P2 anchor position of the KAF11 and KAF8 epitopes, is highly correlated with patients expressing HLA-B*5703 (P ϭ 3.21 ϫ 10 Ϫ8 ).…”
Section: Fig 1 Comparison Of Individual Residue Entropies Between Tmentioning
confidence: 78%
“…The available experimental and epidemiologic data point to structural and functional features of B*5802 that set it apart from the other members of the B58 supertype with regard to its capacity to respond to HIV-1 subtype C peptides. Specifically, it has been suggested that changes in amino acid side chains (94I3T, 95I3L, and 97R3W) in the ␣-2 helix of HLA class I molecules affect the key structures of the antigen binding groove such as the tyrosine bed and the F-pocket (2,12,21,26), thereby impairing the presentation of immunodominant HIV-1 peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Correct tetramer folding was confirmed by staining well-characterized specific cytotoxic T cell lines (18,19). Three of the four NK clones bound to HLA-A*2402 tetramers containing different epitope peptides from HIV-1 nef, HIV-1 gag p17, and human cytomegalovirus (Fig.…”
Section: Kir3dl1 Binds To Hla-a*2402 Tetramersmentioning
confidence: 99%
“…One is that changes in the orientation of D1 and D2 caused by leucine 283 alters the elbow surface to favor interaction with B*5703. The other is that the unusual central bulge of the 11-mer KAF peptide when bound to B*5703 (19) favors binding to the AЈB loop of the D1 domain of 3DL1*005, providing additional interactions that could increase the binding affinity. Further study is needed to determine the contribution of these two potential mechanisms.…”
Section: Structural Models For the Distinctive Hla Class I Specificitmentioning
confidence: 99%